2012
DOI: 10.1007/bf03404239
|View full text |Cite
|
Sign up to set email alerts
|

Overqualification and Risk of All-cause and Cardiovascular Mortality: Evidence From the Canadian Census Mortality Follow-up Study (1991–2001)

Abstract: here is strong evidence demonstrating an inverse association between socio-economic position (SEP) and mortality. 1 In epidemiologic studies, SEP is typically measured as education, occupation or income. 2 These indicators attempt to measure the underlying construct of SEP, and consequently a degree of overlap exists between them. However, these indicators often reflect a specific period in the life-course and measure different dimensions of SEP, and therefore should not be used interchangeably. [2][3][4] Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…These findings are consistent with studies in the general population documenting gradients in mental health by SEP (Frank et al, 2003; Krieger et al, 1997; Marmot & Wilkinson, 2005; Smith et al, 2012). The results of the current study also correspond with the results of a study of sexually active Australian gay men found that major depression was strongly associated with socioeconomic deprivation (Mao et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These findings are consistent with studies in the general population documenting gradients in mental health by SEP (Frank et al, 2003; Krieger et al, 1997; Marmot & Wilkinson, 2005; Smith et al, 2012). The results of the current study also correspond with the results of a study of sexually active Australian gay men found that major depression was strongly associated with socioeconomic deprivation (Mao et al, 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Based on examinations of health gradients in the general population (Frank et al, 2003; Krieger, 2001; Myers, 2009; Smith et al, 2012), the following SEP characteristics were selected as independent variables: household annual income, educational attainment, and employment status. Household annual income (<$11,999, $12,000 – $29,999, $30,000 – $59,999, $60,000+), educational attainment (High school or less [including GED], Some College, College Degree, Post-College), and current employment status (Employed full-time, part-time, unemployed, or other) were measured based on categorizations previously used in other studies using EXPLORE data (Salomon et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The later study (Smith et al . ) included a nationally representative Canadian 15% sample of individuals aged 25 to 64 years with a mortality follow up from 1991 to 2001. Cox proportional hazard regression was used.…”
Section: Introductionmentioning
confidence: 99%